Implementasi Konsep Persinyalan Moving Block dalam lingkup Transportasi Bus Rapid Transit berbasis Wireless Sensor Network - Nursandi Frima Saputra; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Bus is one type of land transportation in Indonesia that can be enjoyed by all people. One of these types of buses has received great attention in the world's transportation mode around the world, namely BRT. In real conditions, Transjakarta uses GPS and sends it to the control center continuously. Therefore, the author implements the concept of moving block in the scope of the BRT transportation mode so that the bus can exchange information about the location of the bus at that time and send it to the control center then the center will give further orders what to do by the bus driver. The result of this research is that the concept of moving block signaling can be implemented on a small scale using a communication protocol with a delay of 0.12 - 0.18 seconds for sending and receiving information data from each system connected to the 802.11 network and the same access point. The results of this value can be a benchmark for developing this research in the future.